2021
DOI: 10.3390/nu13082494
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Predictors of Visceral Adipose Tissue in Women with Polycystic Ovary Syndrome: A Comparison of Methods

Abstract: Visceral adipose tissue (VAT) accumulation, is a part of a polycystic ovary syndrome (PCOS) phenotype. Dual-energy x-ray absorptiometry (DXA) provides a gold standard measurement of VAT. This study aimed to compare ten different indirect methods of VAT estimation in PCOS women. The study included 154 PCOS and 68 age- and BMI-matched control women. Subjects were divided into age groups: 18–30 y.o. and 30–40 y.o. Analysis included: body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), waist-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
1
15
1
Order By: Relevance
“…Regarding the association between eGFRs and the WHt.5R, WC, WHtR, and the WHt.5R were good predictors of the outcomes during metabolic studies of middle-aged and elderly Chinese populations [ 16 ]. The WHt.5R had the best predictive ability when identifying visceral adipose tissue, which could be observed with polycystic ovary syndrome [ 15 ]. Interestingly, two studies have insisted that the WHt.5R is the strongest predictor of cardiometabolic risk, and that the second strongest predictor is WHtR; other metrics included WC, BMI, and WHR [ 6 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the association between eGFRs and the WHt.5R, WC, WHtR, and the WHt.5R were good predictors of the outcomes during metabolic studies of middle-aged and elderly Chinese populations [ 16 ]. The WHt.5R had the best predictive ability when identifying visceral adipose tissue, which could be observed with polycystic ovary syndrome [ 15 ]. Interestingly, two studies have insisted that the WHt.5R is the strongest predictor of cardiometabolic risk, and that the second strongest predictor is WHtR; other metrics included WC, BMI, and WHR [ 6 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two studies have insisted that the WHt.5R is the strongest predictor of cardiometabolic risk, and that the second strongest predictor is WHtR; other metrics included WC, BMI, and WHR [ 6 , 30 ]. Additionally, three other studies reported that the WHtR and WHt.5R were good predictors of outcomes [ 5 , 15 , 31 ]. In relation to these five studies, our results showed that the WHtR was the strongest WC-related obesity metric when compared with BMI or residual BMI for both sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that WTH was independent factor associated with PCOS and have the best discriminatory power in predicting PCOS with an AUC of 0.76. One study showed that it can be used as indirect predictors of visceral obesity in women with PCOS [ 26 ]. Therefore, this abdominal obesity could cause additional disturbances in metabolic and hormonal parameters in PCOS [ 27 ].…”
Section: Main Textmentioning
confidence: 99%
“…PCOS is associated with an increased risk of insulin resistance (IR), hyperinsulinemia, type 2 diabetes mellitus (T2DM), dyslipidemia, obesity and cardiovascular diseases (CVDs) (5,6). Studies on the complexity of this condition have suggested that PCOS patients present with gastrointestinal (GI) disturbances, including abdominal pain, constipation, or bloating, more often than healthy women (7).…”
Section: Introductionmentioning
confidence: 99%